Pengaruh Citra Merek dan Kepercayaan Terhadap Keputusan Pembeliandengan Word Of Mouth Sebagai Variabel Intervening Pada Pengguna Gojek (Studi Pada Mahasiswa Di Yogyakarta) - Jatiningsih, Alfiani; Welsa, Henny; Cahyani, Putri Dwi (Jurnal Manajemen DIVERSIFIKASI, 2022)
The research objective was to determine the effect of brand image, trust influencing purchase decision with word of mouth as an intervening variable in Gojek’s online transportation service. The population in this study of student in Yogyakarta who became Gojek consumers, with a total sample of 100 students. This study uses multiple linear regression analysis techniques in data processing where this technique is used to estimate the value of the dependent variable by using more than one independent variable. The results of the analysis found that there were; (1) Brand image has no significant effect on word of mouth, (2) Trust has a positive and significant effect on word of mouth, (3) Brand image has a positive and significant effect on purchasing decisions, (4) Trust does not have a positive and significant effect on purchasing decisions, (5) Word of mouth has a positive and significant effect on purchasing decisions. In the F test, the value is 31,614 with a significance of 0,000 < 0,05 , so brand image and trust simultaneously affect word of mouth. In the F test, it was obtained a value of 30,434 with a significance of 0,000 < 0,05, so the brand image, trust and word of mouth simultaneously had an effect on purchasing decisions.